The effectiveness of Quizlet application towards students’ motivation in learning vocabulary - Muhammad Rizky Setiawan; Pangesti Wiedarti (Universitas Syiah Kuala, 2020)
Increasing motivation is necessary for students in learning English vocabulary. The higher motivation the students gain, the bigger success they achieve in mastering vocabulary. However, most students in senior high schools have less motivation in learning vocabulary, especially in memorizing them. Thus, the teachers need to discover appropriate media for increasing their motivation. Some applications can be used through the smartphone as the need for vocabulary learning. The purpose of this study is to investigate the effectiveness of using Quizlet Application as the media for increasing the students’ motivation in learning vocabulary. Nonequivalent control group design was used in this research. The participants were 65 students who were divided into the experimental and the control groups. The students’ motivation was observed during the process of vocabulary learning by using the observation checklist. In processing the data, the Wilcoxon test was used. The results show the use of Quizlet Application is effective to increase the students’ motivation in learning vocabulary. Students felt more enthusiastic, did not get bored easily, and thus showed high interest when learning vocabulary via the app. They also did the tasks provided in that application independently.